(untitled) (Indian Journal of Arid Horticulture, 2025)
Ber is an important fruit crop in the arid regions of Asia and Africa. Some physical and mechanical properties of six ber cultivars namely Umran, Ilaichi, Gola, Mundia, Goma kirthi and Banarasi karka were determined. The geometrical mean diameter of fruits varied from 2.65 to 4.85 cm. The sphericity varied from 0.73 to 0.88 among cultivars and the fruits of Gola were more spherical than the fruits of other cultivars. The surface area, volume, average weight and firmness of Umran fruits were significantly higher, 74.04 cm2, 89.90 cm3, 56.66 g and 6.80 N, respectively than the other fruits. The cutting strength of Goma kirti fruits was found to be better than the fruits of other cultivars.